Investigation of Code-Switching Used by Young-Famous Indonesian YouTubers in Travel Content Videos - Yunisrina Qismullah Yusuf; Ika Apriani Fata; Deafi Denilda; Saiful Marhaban Saiful Marhaban; Abdulhakim Saidu Abdulhakim Saidu (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2025)
In travelling videos, people tend to do code-switching, yet there is limited study to examine code-switching in YouTube during travelling time. This study focused on filling in the gap by analysing code-switching by young and famous Indonesian YouTubers in travel content videos. Five informants through purposive sampling were chosen, and we employed a descriptive qualitative method, drawing on the frameworks of Gumperz and Hoffmann. The results revealed that famous Indonesian YouTubers utilised four code-switching types: inter-sentential switching, intra-sentential switching, tag-switching and determining consistency with the previous speaker. Intra-sentential Switching was the most popular code-switching strategy among YouTubers, and it indicates the utility in ordinary communication and to interact daily. However, consistency with the previous speaker was the least to be determined, signifying that YouTubers like to proceed to new topics during vlogging rather than repeating the words of earlier speakers. This study also discovered five code-switching functions: reiteration, interjection, addressee specification, message qualification, and personalization vs objectification. YouTubers mostly used interjections in English tags to strengthen sentences so viewers may remember the vlogging content easily. The quotation function has never been found denoting Youtubers' limited schemata for relating content to scientific knowledge. Further studies are encouraged to explain the phenomenon of CS in other social media and compare senior YouTubers with young YouTubers in vlogging or podcasting.